Cysteine-Rich Angiogenic Inducer 61 Serves as a Potential Serum Biomarker for the Remission of Adult-Onset Still's Disease - Su, Yutong; Wang, Zhihong; Ye, Junna; Feng, Tienan; Wang, Fan; Chi, Huihui; Zhou, Zhuochao; Hu, Qiongyi; Liu, Honglei; Cheng, Xiaobing; Shi, Hui; Teng, Jialin; et al. (Frontiers in Medicine, 2019)
Objective Adult-onset Still’s disease (AOSD) is a rare, polygenic, systemic autoinflammatory disease. The aim of this study is to evaluate the serum levels of cysteine rich angiogenic inducer 61 (Cyr61), a secreted, extracellular protein in AOSD patients. Methods A total of 60 AOSD patients (39 of active phase and 21 of inactive phase), 16 rheumatoid arthritis patients and 34 six- and age-matched healthy control subjects (HC) were enrolled in the study. The data of the clinical manifestations and laboratory examinations were collected. The serum levels of Cyr61, IL-17 and IL-37 were detected by ELISA assay and the serum levels of IL-10, IL-1β, IL-6, IL-18, and TNF-α were examined by electrochemiluminescence assay. Results The serum levels of Cyr61 were significantly increased in inactive AOSD than in active patients and HCs, and the levels of Cyr61 were dramatically increased after treatment. The levels of Cyr61 were inversely correlated with systemic score, the counts of leukocyte and neutrophil, and the levels of inflammatory cytokines (IL-1β, IL-6 and IL-17). Moreover, the levels of Cyr61 were higher in patients without the clinical symptoms of fever, skin rash, sore throat, arthralgia and lymphadenopathy compared with patients with these symptoms. Conclusion The serum levels of Cyr61 were inversely correlated with disease activity in AOSD patients, thus we proposed that Cyr61 was a biomarker for the remission of AOSD.